Public Innovation Policy in the Pharmaceutical Industry: the Cases of the EU and USA - Z. A. Mamedyarov (Модернизация, инновация, развитие, 2017)
Purpose: the main purpose of this article was to study the modern tools of the public innovation policy in the global pharmaceutical industry (US and EU cases), which is one of the most knowledge-intensive sectors of the global economy. During the study, it was necessary to achieve the following objectives: to identify main components of the innovation policy in the sector, to consider the role of intellectual property protection, measures of innovation support, regulatory control and other factors, and, also, to identify comparative characteristics of innovation processes within the US and the EU pharmaceutical sector. Methods: this article is based on a qualitative comparative study of the US and EU innovation policy in the pharmaceutical industry. Industryoriented innovation support measures (i.e. levels of private and public financing) have been quantitatively analyzed, including the evaluation of the levels of R&D productivity; also, a comparative study of the pharma patent statistics in the leading countries have been performed. This article highlights the problems of intellectual property protection, which remains an important source of financial stability for major pharma companies being the basis for new innovation agenda. Low R&D productivity and high costs of new innovative drugs together emphasize the significance of the analysis of current innovation processes within the pharmaceutical industry, and could open the way for building more effective managerial and business processes. Results: the global pharmaceutical industry today is under thorough control of government regulators and civil society organizations seeking to improve mechanisms of the drugs distribution, in order to make drugs more accessible, safe and clean. This high regulation level impedes innovation within existing pharma business models, and leads to high costs of the newest drugs. The study revealed that successful pharmaceutical innovation today requires significant expenses on the largest companies’ side. The patent statistics revealed the increasing role of developing countries, which are nevertheless still poorly involved in the pharma innovation processes. Comparison of the US and the EU innovation policies showed underdeveloped venture capital market of the EU and relatively high level of government regulation. Conclusions and Relevance: companies go through an intense period of mergers and acquisitions, and are looking for new ways of performing R&D and the expansion of product markets. Public sector of the developed countries contributes to the development of new partnerships and collaborations, hoping to spur the creation of new jobs and competencies. Pharmaceutical companies are actively collaborating with regional research institutes, universities and hospitals. Despite this high level of activity, key actors and government regulators have yet to come to an understanding of new mechanisms to stimulate innovation, taking into account the development of biotechnology, generic drugs and the growing need to revise current business models of the largest pharmaceutical companies.